Pro- and anti-tumorigenic functions of the senescence-associated secretory phenotype. (2nd December 2019) - Lau, Lena; David, Gregory
ABSTRACT: Introduction : Cellular senescence is a stable form of cell cycle exit. Though they no longer divide, senescent cells remain metabolically active and secrete a plethora of proteins collectively termed the senescence-associated secretory phenotype (SASP). Although senescence-associated cell cycle exit likely evolved as an anti-tumor mechanism, the SASP contains both anti- and pro-tumorigenic potential. Areas covered : In this review, we briefly discuss the discovery of senescent cells and its relationship to cancer and aging. We also describe the initiation and regulation of the SASP upon senescence stimulus onset. We focus on both the pro- and anti-tumorigenic properties of the SASP. Finally, we speculate on the potential benefits of therapy-induced senescence combined with selective SASP inhibition for the treatment of cancer. Expert opinion : Further identification and characterization of the SASP factors that are pro-tumorigenic and those that are anti-tumorigenic in specific contexts will be crucial in order to develop personalized therapeutics for the successful treatment of cancer.